Integration of Character Education Values for Students through Learning Peusijuek Traditions Based on Local Wisdom - Rachmatsyah Rachmatsyah; Sukirno Sukirno; Usman Usman (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study examines the importance of strengthening character education and knowledge skills in students' understanding of local wisdom based on the culture of peusijuek customs carried out by the people of Aceh. This research uses a descriptive method of qualitative. The method reveals a state that takes place according to qualitative research built on the formulation of certain situations, such as those living by a particular individual or social group, and relevant to the study's objectives. Secondary sources and participant observation methods are used for data collection. Verification and inference are the two main methods of data analysis. There are three components to the study's findings. First, the type of peusijeuk carried out in certain activities, such as peusijuek meulangga, peusijuek pade bijeh, peusijuek peudong rumoh, peusijuek tempat tinggai, peusijuek keurubeuen, peusijuek new vehicles and peusijuek performing the hajj; Second, the character values possessed by students in the Acehnese cultural customary course are the value of peusijuek tolerance, religious values, cooperation values and social values; Third, the value of local wisdom in the implementation of peusijeuk, namely talam, clok (calok), serving hoods (sangee), rice, unsalted flour, on manek-mano, on sijuek, naleung samboe and bu leukat. The conclusion is that Peusijeuk is part of the lecture material on traditional Aceh culture as one of the rituals related to religious beliefs that must be carried out. The values of character education in the peusijuek tradition based on local wisdom include the value of tolerance, religious value, social value, and the value of cooperation.